Profiling the countermovement jump characteristics of basketball players across competitive levels and playing positions - Suarez-Balsera, C.; Ferioli, D.; Marín-Cascales, E.; Rago, V.; Spyrou, K.; Martínez-Serrano, A.; Di Mauro, D.; Marín, J. M.; Alcaraz, P. E.; Freitas, T. T. (Journal of Human Kinetics, 2025)
This study aimed to examine different force-time derived variables of the countermovement jump (CMJ) in adult, male basketball players of different competitive levels and playing positions. At the beginning of the pre-season, 78 players from two competitive levels (professional and semi-professional) completed a CMJ test on a force plate. Linear mixed models were used to compare a total of 21 metrics across competitive levels and playing positions. Professional players jumped significantly higher (p = 0.022) than semi-professionals. No differences were observed in the variables related to the eccentric phase. Four concentric phase variables (i.e., absolute peak force [p < 0.001], absolute and relative peak power [p < 0.001 and p = 0.037, respectively] and peak velocity [p = 0.036]) were superior in professional in comparison to semi-professional players. Regarding the playing position, centers presented significantly larger deceleration phase duration than guards (p = 0.042). Centers reported higher absolute eccentric peak force than guards (p = 0.013). In the concentric phase, centers reported larger concentric duration than forwards (p = 0.011) and guards (p = 0.002). Guards produced lower absolute peak force compared to centers (p = 0.004) and forwards (p = 0.025). Furthermore, centers were characterized by lower levels of relative peak force (p = 0.013), but higher levels of absolute peak power compared to guards (p = 0.003). In conclusion, jump height, and only four concentric-phase metrics were found to discriminate between competitive levels. Additionally, the eccentric deceleration phase duration, absolute eccentric peak force, concentric duration, absolute and relative peak force and absolute peak power discriminated between playing positions. Practitioners should conduct thorough CMJ analyses and consider these metrics from a performance and talent identification perspective.